CSF and Serum Levels of Inflammatory Markers in PD: Sparse Correlation, Sex Differences and Association With Neurodegenerative Biomarkers - Lerche, Stefanie; Zimmermann, Milan; Wurster, Isabel; Roeben, Benjamin; Fries, Franca Laura; Deuschle, Christian; Waniek, Katharina; Lachmann, Ingolf; Gasser, Thomas; Jakobi, Meike; Joos, Thomas O.; Schneiderhan-Marra, Nicole; et al. (Frontiers in Neurology, 2022)
Background: An involvement of the central-nervous and peripheral, innate and adaptive immune system in the pathogenesis of Parkinson’s disease (PD) is nowadays well established. Objectives: We face several open questions in preparation of clinical trials aiming at disease-modification by targeting the immune system: Do peripheral (blood) inflammatory profiles reflect central (CSF) inflammatory processes? Are blood/CSF inflammatory markers associated with CSF levels of neurodegenerative/PD-specific biomarkers? Methods: Using a multiplex assay we assessed 41 inflammatory markers in CSF/serum pairs in 453 sporadic PD patients. We analysed CSF/serum correlation as well as associations of inflammatory markers with clinical outcome measures (UPDRS-III, H&Y, MoCA) and with CSF levels of α-synuclein, Aβ1-42, t-Tau, p181-Tau and NFL. All analyses were stratified by sex as the immune system shows relevant sex-specific differences. Results: Correlations between CSF and serum were sparse and detected in only 25% (9 out of 36) of the analysable inflammatory markers in male PD patients and in only 38% (12 out of 32) of female PD patients. The most important pro-inflammatory mediators associated with motor and cognitive decline as well as with neurodegenerative/PD-specific biomarkers were FABP, ICAM-1, IL-8, MCP-1, MIP-1-beta, and SCF. Results were more robust for CSF than for serum. Interpretation: Levels of central-nervous and peripheral inflammatory markers might be regulated independently of each other with CSF inflammatory markers reflecting CNS pathology more accurately than peripheral markers. These findings along with sex-specific characteristics have to be considered when designing clinical trials aiming at disease-modification by targeting the immune system.